2014
DOI: 10.1123/jpah.2011-0257
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Survival After Cancer Diagnosis in Men

Abstract: Background The number of cancer survivors is increasing rapidly; however, little is known about whether engaging in physical activity after a cancer diagnosis is associated with lower mortality rates in men. Methods We conducted a prospective cohort study of 1,021 men (mean age, 71.3 years) who were diagnosed with cancer (other than non-melanoma skin cancer). Men reported their physical activities (walking, stair climbing, and participation in sports and recreational activities) on questionnaires in 1988, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Among male cancer survivors, higher levels of physical activity have also been associated to both all-cause and cancerspecific mortality (7). Although increased physical activity was associated with a reduced risk of prostate cancer in a recent meta-analysis (8), very little is known about the association between post-diagnosis physical activity and survival among patients with prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Among male cancer survivors, higher levels of physical activity have also been associated to both all-cause and cancerspecific mortality (7). Although increased physical activity was associated with a reduced risk of prostate cancer in a recent meta-analysis (8), very little is known about the association between post-diagnosis physical activity and survival among patients with prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Milne, Gordon, Guilfoyle, Wallman, and Courneya (2007) examined how urban or rural contexts affect quality of life for survivors; regardless of setting, they found that physical activity was correlated with improved quality of life. Although engaging in more physical activity is associated with greater reductions in mortality rates, even the recommended amount of weekly physical activity has been linked to significantly lower mortality rates (Lee et al, 2014). Rabin, Pinto, Trunzo, Frierson, and Bucknam (2006) found that previously sedentary survivors who participated in a 12-week physical activity intervention showed similar improvement in physical functioning as those who independently undertook regular exercise.…”
mentioning
confidence: 99%
“…In this case, it also seems that the amplitude of physical activity reduced the risk of both cancer-related mortality and cardiovascular disease [11] . However, this was not found in PDAC [12] .…”
Section: Discussionmentioning
confidence: 85%
“…Regarding physical activity, which could modify the depressive state, there are no conclusive data on the real impact on the immune system. Finally, although there is experience that correlates the amplitude of physical activity with the reduction of the risk of cancer-related and cardiovascular mortality [11] , this has not been reported on PDAC [12] .…”
Section: Introductionmentioning
confidence: 89%